SELF-PACED LEARNING WITH 3D HUMANOID VIRTUAL TUTORS - Zysk, Wolfgang; Filkov, Rumen (European Scientific Journal, ESJ, 2014)
For acquiring specific vocational skills, it is essential that trainees are able to observe their trainers closely while these demonstrate particular working movement processes in an exemplary fashion. It would further be desirable if each trainee was able to absorb these observations in accordance to his or her own, individual learning habits and capabilities. Yet circumstances in real-life classroom situations often make individual supervision of each trainee to a large extent impossible. Therefore computer-animated 3D humanoid characters, precisely emulating the correct, realistic behavior of trainers, with a computer program which can be operated by the trainee in a self-paced mode, could present a viable training aid. Our work has consequently been focused on the conceptualization and creation of tools to realize visible aspects of the training process for the purpose of self-paced learning through 3D humanoid characters. After a short introduction to the didactical concept, this paper presents the creation and the preceding development of such a self-paced learning tool.